Quantifying internal CO2 recycling for high-rate carbon capture in mixotrophic Scenedesmus acuminatus - Muhammad Muzammil Sultan; Muhammad Mubashar; Hira Ashfaq; Jing Li; Xuezhi Zhang (Bioresource Technology, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

Artificial photosynthesis of H2O2 with covalent organic frameworks: From structural design to catalytic function - Ajmal Khan; Yasser A. Alassmy; Mohammed Qasem Alfaifi; Marwan M. Abduljawad; Sultan A. Alshuhri; Irshad Ahmad; Qinyun Huang; Yuyu Liu; Muhammad Arshad (Journal of Environmental Chemical Engineering, 2026)

Defect engineering of complex perovskite oxide via plasmonic metal (La0.6Sr0.4Fe0.7Cu0.1Co0.2O3) in polymeric network hydrogel for enhanced solar steam generation - Naila Arshad; Muhammad Sultan Irshad; Lamia Abu El Maati; Afraa Alotaibi; Van-Duong Dao; Naveed Mushtaq; Muneerah Alomar (Journal of Environmental Chemical Engineering, 2026)

Graft incompatibility in fruit trees in early detection: integrating physiological, molecular, and technological approaches - Muhammad Hamza; Dilek Soysal; Izhar Ullah; Yaqoob Sultan; Erol Aydin; Hüsnü Demirsoy; Heba I. Mohamed (Planta, 2026)

Retraction Note: Bond graph analysis of a three-link physiological motor control system: integrating simulation and muscle behavior - Armeen Saeed; Nadia Sultan; Najam-ul-Islam Muhammad; A. M. Mughal (Biological Cybernetics, 2026)

Numerical Analysis of Altitude Effects on Single-Cylinder Two-Stroke UAV Engine Performance - Muhammad Nouman Rashid; Faiq Said; Syed Ghafoor Shah; Muhammad Bilal; Hamza Sultan; Muhammad Qail (Next Research, 2026)

Tailoring SrFeO3-δ cathodes via Nd and Cu doping for boosting ORR activity for high-performance LT-PCFCs below 600 °C - Naveed Mushtaq; Wu Ping; Badriah S. Almutairi; Sajid Rauf; M.A.K Yousaf Shah; Muhammad Sultan Irshad (Fuel, 2026)

Multilevel barriers to antimicrobial stewardship in tertiary care hospitals: A comparative systematic scoping review of high-income versus low-/middle-income countries evidence mapped by study design and healthcare professionals - Azfar Athar Ishaqui; Zikria Saleem; Tauqeer Hussain Mallhi; Sultan M. Alshahrani; Khalid Orayj; Salman Ashfaq Ahmad; Rayah Asiri; Emad Ali Alsaleh; Muhammad Imran; Mohammed Ali Kaddoura; Bilal Jawed; Narendar Kumar; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A V-shaped CNT-decorated LiNi0.8Co0.15Al0.05O2 photothermal fabric for high-efficiency solar steam generation and desalination - Huibin Guan; Naila Arshad; Bushra Shakoor; Najah Alwadie; Xiaochao Fan; Ruijing Shi; Van-Duong Dao; Nang Xuan Ho; Jian Zhang; Muhammad Sultan Irshad; Calvyn T. Howells; Phuong Anh Lam; et al. (Journal of Environmental Chemical Engineering, 2026)

A Critical Review on Advance Molecular Distortion Techniques for Textile Wastewater Treatment in Pakistan - Sahrish Ashraf; Muhammad Sultan; Muhammad Wakil Shahzad; Muhammad Imran; Rana M. A. Kanwar; Muhammad Nauman Ashraf; Zahid Mahmood Khan; Zubair Khaliq; Muhammad Bilal Qadir (Water, Air, & Soil Pollution, 2026)

Phosphorus availability modulates OsPTF1 expression in Oryza sativa L. - Muhammad Saeed Ahmad; Zulfiqar Ali; Rizwana Maqbool; Sultan Habibullah Khan (Cereal Research Communications, 2026)

Geospatial analysis of surface urban heat island dynamics and land use changes in Pakistan using multi-spectral indices - Awais Ali; Bilal Hussain; Muhammad Naveed; Bader Alshehri; Abdul Ghafoor; Zeeshan Zafar; Faisal Sultan Qadri (Advances in Space Research, 2026)

Recent Advances in p-Type Nickel Oxide (NiO) for Solar-Light-Driven Photocatalytic Degradation of Organic Pollutants - Mansoor sultan; Nisar Ali; Muhammad Naseem; Shah Ihsan; Mazharul islam; Abdul kareem; Shahbaz Khan; Bakht Muhammad Khan; Fawad khan; Farman Ali; Adnan Khan; Rayya Ahmed Al Balushi; et al. (Water, Air, & Soil Pollution, 2026)

Novel Silver Nickel Ferrite Nanocomposite: Synthesis, Characterization, Comparative Remediation of Eriochrome Black T - Maria Khan; Sultan Muhammad; Ammara Aftab; Zooraisha Adeel; Muhammad Waseem (Water, Air, & Soil Pollution, 2026)

Association of oral metoprolol exposure during heart failure hospitalization with death or readmission at 28-days and 6-months using a propensity score overlap-weighted EHR analysis - Azfar Athar Ishaqui; Emad Ali Alsaleh; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Khalid Orayj; Rayah Asiri; Sultan M. Alshahrani; Salman Ashfaq Ahmad; Narendar Kumar; Adnan Iqbal; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comparative disproportionality signals for methotrexate monotherapy versus methotrexate combined with hydroxychloroquine, leflunomide, or sulfasalazine in rheumatoid arthritis: newly highlighted signals evaluated using drug information safety profiles - Azfar Athar Ishaqui; Khalid Orayj; Zeeshan Ahmed; Salman Ashfaq Ahmad; Sultan M. Alshahrani; Rayah Asiri; Adnan Iqbal; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Rethinking lice management at the human–animal interface: challenges, green alternatives, and the road ahead - Rimsha Jamil; Muhammad Imran; Muhammad Adnan Sabir Mughal; Rao Zahid Abbas; Muhammad Umar Ijaz; Muhammad Kasib Khan; Asghar Abbas; Farhan Ahmad Atif; Sultan Ali (International Journal of Tropical Insect Science, 2026)

Myricetin as a potential therapeutic agent against Pseudomonas aeruginosa : inhibition of biofilm formation, quorum sensing, and virulence factor production - Sallah A. Al Hashedi; Saif M. Dmour; Hamad Sarheed Galut; Ayman Daifallah Ismail Alsheikh; Mohammad H. Abukhalil; Sham Ma’aitah; Najeeb S. Al-Zoreky; Khaled M.A. Ramadan; Muhammad Naeem Sattar; Zafar Iqbal; Adil Alshoaibi; Sultan A. M. Saghir (Biofouling, 2026)

Corrigendum to “Underground geological sequestration of carbon dioxide (CO2) and its effect on possible enhanced gas and oil recovery in a fractured reservoir of Eastern Potwar Basin, Pakistan” [Sci. Total Environ. 905 (2023) 167124] - Anaiz Gul Fareed; Fabio De Felice; Antonella Petrillo; Muhammad Arsalan Sultan; Zafar Khan Jalalzai (Science of The Total Environment, 2026)

Mixotrophic microalgae-based wastewater nutrient removal: A systematic analysis of historical evolution, current progress, challenges, and prospects - Muhammad Mubashar; Rabail Zulekha; Muhammad Muzamil Sultan; Pengfei Cheng; Wenguang Zhou; Xuezhi Zhang (Journal of Water Process Engineering, 2026)

Remediating Methylene Blue and Eriochrome Black T by Acid Activated Multiwalled Carbon Nanotubes - Sultan Muhammad; Zubaah Khalid; Maria Khan; Ammara Aftab; Muhammad Waseem (International Journal of Environmental Research, 2026)

mcr gene family evolution and structural mechanisms of colistin resistance: from mcr-1 to emerging variants - Muhammad Shahid Mehmood; Uthpala Kavindi Rupasinghe Koggala Marakkalage; Tabish Arif; Fariha Javaid; Muhammad Ali Abid; Muntha Shahid; Anwar Parvez; Muhammad Nabeel Saddique; Sultan Ali (Archives of Microbiology, 2026)

Machine learning-guided discovery of mitogen-activated protein kinase 7 (MAPK7 inhibitors): integrating virtual screening, docking, and molecular dynamics simulations - Chandni Hayat; Amar Ajmal; Nayab Gul; Muhammad Numan; Haleema Bibi; Naveed Akhtar; Laiba Sultan; Arif Ali; Muhammad Tahir Khan; Muhammad Saqib (In Silico Pharmacology, 2026)

Neuro-computational surrogates for aqueous fractional-order nekton-plankton spatiotemporal dynamics under toxicant stress, refuge efficacy, and nutrient flux modulation - Adil Sultan; Chuan-Yu Chang; Muhammad Junaid Ali Asif Raja; Adiqa Kausar Kiani; Muhammad Shoaib; Muhammad Asif Zahoor Raja (Water Research, 2026)

Is ozone pretreatment in algal-laden water adequately evaluated, or does synchronous O₃/Fe(II) offer a better alternative? - Zimin Wang; Shi Zhang; Shaozhe Cheng; Muhammad Muzamil Sultan; Lei Zhang; Haiyang Zhang; Nanqin Gan; Xuezhi Zhang (Journal of Hazardous Materials, 2026)

Ameliorating effect of veratric acid against mercury-induced neurologic deficit and reproductive toxicity in female rats - Saira Saeed; Qurat-Ul-Ain; Ammara Saleem; Muhammad Imran Khan; Kanwal Akhtar; Aslam Khan; Muhammad Furqan Akhtar; Amir Bouallegue; Mohammed Bourhia; Sultan F. Kadasah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Toxic Metals in the Workplace: Assessing Heavy Metal Contaminants in Indoor Dust of Auto Parts Stores and Their Impact on Health of Employees - Nadeem Ali; Sultan H. Alamri; Jahan Zeb; Mohammad Rehan; Nisreen Rajeh; Nabil Alhakamy; Mohamed I. Orif; Muhammad Imtiaz Rashid; Syed Ali Musstjab Akber Shah Eqani; Hani Z. Asfour (Water, Air, & Soil Pollution, 2025)

Predictive analysis of plankton population dynamics in marine biosphere: a nonlinear ARX neural network for the carbon-thermal-nutrient-plankton asymmetric multifactor system for global warming - Adil Sultan; Muhammad Junaid Ali Asif Raja; Chuan-Yu Chang; Chi-Min Shu; Adiqa Kausar Kiani; Muhammad Shoaib; Muhammad Asif Zahoor Raja (Environmental Monitoring and Assessment, 2025)

A hybrid 3D CNN-LSTM model with soft spatial attention mechanism for accurate hyperspectral image classification - Mohamed Sultan Mohamed Ali; Md Sakib Bin Islam; Molla E. Majid; Saad Bin Abul Kashem; Amith Khandakar; Muhammad E.H. Chowdhury (Remote Sensing Applications: Society and Environment, 2025)

Understanding flood behavior in the Kashmir Himalayas through copula-driven models - Ishfaq Gujree; Shafique ur Rehman; Joshal K. Bansal; Ningsheng Chen; Aijaz Ahmad Reshi; M. Sultan Bhat; Muhammad Atiq Ur Rehman Tariq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Side structural regulation strategy of 3D gear evaporators for enhanced solar water evaporation and salt harvesting - Junyang Tao; Zihan Feng; Shan Zhai; Suji Huang; Yi E; Fengshuai Zhu; Liangyou Lin; Jingwen Qian; Muhammad Sultan Irshad; Xianbao Wang (Desalination, 2025)

Beyond brine: Super salt-resistant solar evaporator via inclined brine regulation and sustainable energy transition - Yuchen Gan; Zihan Feng; Ruilei Xiao; Muneerah Alomar; Dang Viet Quang; Nang Xuan Ho; Naila Arshad; Junyang Tao; Saif Ur Rehman; Xianbao Wang; Van-Duong Dao; Muhammad Sultan Irshad (Desalination, 2025)

3D arched solar evaporator with latent heat recovery for high-performance seawater desalination and sustainable saline agriculture - Yi E; Naila Arshad; Zhengguo Jiao; Junyang Tao; Jingwen Qian; Tao Mei; Muhammad Sultan Irshad; Xianbao Wang (Desalination, 2025)

Recent advances in conducting polymers for hybrid solar-driven evaporation systems: Fundamentals, innovations, and applications - Bushra Shakoor; Muhammad Sultan Irshad; Uzma Ghazanfar; Humaira Razzaq; Naila Arshad; Ghazala Maqsood; Iftikhar Ahmed; Muhammad Atif Ali; Muhammad Sohail Asghar; Irshad Hussain; Tao Mei; Tran Vinh Dieu; et al. (Chemical Engineering Journal, 2025)

NiMn-LDH/polypyrrole photothermal structures for interfacial solar steam generation - Ghazala Maqsood; Muhammad Sohail Asghar; Bushra Shakoor; Muneerah Alomar; Muhammad Atif Ali; Yi E; Tao Mei; Muhammad Sultan Irshad; Xianbao Wang (Chemical Engineering Journal, 2025)

Modulating condensate efficiency with hybrid solar evaporation: Synergistic photothermal and joule heating for high-performance water harvesting - Yi E; Naila Arshad; Zhengguo Jiao; Junyang Tao; Muneerah Alomar; Jingwen Qian; Tao Mei; Nang Xuan Ho; Van-Duong Dao; Muhammad Sultan Irshad; Xianbao Wang (Chemical Engineering Journal, 2025)

Jasmonic Acid: A Key Elicitor of Cold Stress Tolerance in Horticultural Crops - Izhar Ullah; Muhammad Hamza; Noor ul Ain; Heba I. Mohamed; Murad Muhammad; Yaqoob Sultan; Muskan Alam Khan; Abdul Basit (Journal of Plant Growth Regulation, 2025)

Microplastics in two commercial marine fish species: A pilot study from the Arabian Sea - Nabia Saleem Khan; Imrana Niaz Sultan; Afrasiab Khan Tareen; Muhammad Waseem Khan (Environmental Monitoring and Assessment, 2025)

Highly efficient and durable solar-driven desalination using MoS2 aerogels enabled by PEG-induced hydration modulation - Jiameng Zhang; Zhenzhen Guo; Haoran Zhang; Tianxiang Zhou; Muneerah Alomar; Xiaochao Fan; Uzma Ghazanfar; Phan Thi Dien; Bui Thi My Duyen; Muhammad Sultan Irshad; Van-Duong Dao (Journal of Environmental Chemical Engineering, 2025)

Tailoring polymerized fabrics for sustainable water-driven electricity and salt-water separation membrane - Zhenzhen Guo; Jiameng Zhang; Haoran Zhang; Wanqing Zhang; Naila Arshad; Muneerah Alomar; Nang Xuan Ho; Xiaochao Fan; Muhammad Sultan Irshad; Van-Duong Dao; Xianbao Wang (Desalination, 2025)

Clean water and energy co-generation via alternative renewables - Xiaochao Fan; Bushra Shakoor; Han Yusen; Shi Ruijing; Yang Mingtao; Li Ziqiang; Naila Arshad; Uzma Ghazanfar; Van-Duong Dao; Jian Zhang; Muhammad Sultan Irshad; Calvyn T. Howells; et al. (Chemical Engineering Journal, 2025)

Interactions between micro(nano)plastics and natural organic matter: implications for toxicity mitigation in aquatic species - Naima Hamid; Marriya Sultan; Muhammad Junaid; Stuart Cairns; Iain Robertson; Houda Javed; De-Sheng Pei (Aquatic Toxicology, 2025)

Structural and functional insights into Jasmonate ZIM-domain 2 (GhJAZ2) interactions in cotton fiber development via Jasmonic acid signaling - Muhammad Sulyman Saleem; Sultan Habibullah Khan; Zunaira Afzal Naveed (Plant Gene, 2025)

Thermodynamic evaluation of advanced adsorbents for thermally-driven atmospheric water harvesting system in diverse climatic conditions - Muhammad Sultan; Aïssa Rezzoug; Muhammad Aleem (International Journal of Refrigeration, 2025)

Pore-Filling behaviors and lateral propagation of CH4 and CO2 hydrates forming in microfluidic porous media - Muhammad Habiburrahman; Wei Yu; Kun Ge; Jiaqi Wang; Abdullah S. Sultan (Chemical Engineering Journal, 2025)

Spatiotemporal dynamics and environmental drivers of fractional vegetation cover in a Semi-Arid region using machine learning - Shoaib Ahmad Anees; Kaleem Mehmood; Sultan Muhammad; Mi Luo; Fahad Shahzad; Waseem Razzaq Khan (Theoretical and Applied Climatology, 2025)

Advancing forest fire prediction: A multi-layer stacking ensemble model approach - Fahad Shahzad; Kaleem Mehmood; Shoaib Ahmad Anees; Muhammad Adnan; Sultan Muhammad; Ijlal Haidar; Jamshid Ali; Khadim Hussain; Zhongke Feng; Waseem Razzaq Khan (Earth Science Informatics, 2025)

Functionalized carbon nanotubes interconnected with metal-organic frameworks for in-situ solar-driven evaporation and salt recovery from seawater - Muhammad Sohail Asghar; Muhammad Sultan Irshad; Naila Arshad; Maryam Al Huwayz; Muneerah Alomar; Ghazala Maqsood; Muhammad Atif Ali; Uzma Ghanzanfar; Muhammad Sabir; Jinhua Li; Van-Duong Dao; Nang Xuan Ho; et al. (Water Research, 2025)

Design of a fractional-order environmental toxin-plankton system in aquatic ecosystems: A novel machine predictive expedition with nonlinear autoregressive neuroarchitectures - Muhammad Junaid Ali Asif Raja; Adil Sultan; Chuan-Yu Chang; Chi-Min Shu; Muhammad Shoaib; Adiqa Kausar Kiani; Muhammad Asif Zahoor Raja (Water Research, 2025)

Corrigendum to “Dual-modification strategy for efficient inverted perovskite solar cells via thermally induced liquid crystals and boosting of phenethylammonium by carbazole” [Chem. Eng. J. 516 (2025) 163918] - Bilal Mehmood; Chen Zhang; Shan Wu; Jiangying Lu; Xu Zheng; Wei Jiang; Kamran Amin; Shudi Lu; Muhammad Iftikhar Khan; Muhammad Sultan; Tanveer Ashraf; Zhijie Wang; et al. (Chemical Engineering Journal, 2025)

Oxidative phosphorylation and breast cancer progression: insights into PGC-1α’s role in mitochondrial function - Rihab Akasha; Jerlyn Apatan Enrera; Syeda Bushra Fatima; A. M. Hegazy; Weiam Hussein; Muhammad Nawaz; Maali D. Alshammari; Sultan Almuntashiri; Najah Albadari; Mohammed Khaled Bin Break; Rahamat Unissa Syed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A Novel Prednisolone-Loaded Layer-by-Layer Nanoparticles (LBL-NPs) for Rheumatoid Arthritis: Optimization and Therapeutic Evaluation - Jamal Moideen Muthu Mohamed; Durgaramani Sivadasan; Ahmad Salawi; Muhammad H. Sultan; Pooja Muralidharan; Krishnaraju Venkatesan; Yahya I. Asiri; Mona Qushawy; Gayathri Pandurangam; Farid Menaa (Journal of Pharmaceutical Innovation, 2025)

Anthropogenic dust pollution influences leaf and root morpho-anatomical traits by altering the metabolism and biochemical properties of indigenous vegetation - Muhammad Asim Sultan; Iftikhar Ahmad; Muhammad Arif; Saima Sadaf; Muhammad Kamran; Toqeer Abbas; Shifa Shaffique; Mansour K. Gatasheh (Environmental Geochemistry and Health, 2025)

Determination of heavy metals and morphoanatomical characteristics of the monocots Aristida mutabilis and Cenchrus ciliaris in the dust-contaminated stone crushing industry of Sargodha, Pakistan - Muhammad Asim Sultan; Iftikhar Ahmad; Muhammad Arif; Saud Alamri; Manzer H Siddiqui; Saima Sadaf; Muhammd Kamran (Environmental Monitoring and Assessment, 2025)

A critical review of opportunities and challenges of solid waste management in an emerging economy- evidence from Pakistan - Sajid Rashid; Hameeda Sultan; Wajid Rashid; Bushra Danish Talpur; Roberto Xavier Supe Tulcan; Muhammad Tariq Khan; Eve Bohnett; Muhammad Safar Korai; Lixiao Zhang (Environmental Development, 2025)

Dual-modification strategy for efficient inverted perovskite solar cells via thermally induced liquid crystals and boosting of phenethylammonium by carbazole - Bilal Mehmood; Chen Zhang; Shan Wu; Jiangying Lu; Xu Zheng; Wei Jiang; Kamran Amin; Shudi Lu; Muhammad Iftikhar Khan; Muhammad Sultan; Tanveer Ashraf; Zhijie Wang; et al. (Chemical Engineering Journal, 2025)

Preparation, Characterization and Removal of Acid Blue 129 and Erioglaucine Dyes from Aqueous Solution by Corn Cob Based Activated Carbon - Sultan Alam; Najeeb ur Rahman; Muhammad Ilyas; Iram --; AlSaba Gul; Muhammad Zahoor; Muhammad Naveed Umar; Riaz Ullah; Essam A. Ali (Bulletin of Environmental Contamination and Toxicology, 2025)

Spatial and temporal vegetation dynamics from 2000 to 2023 in the Western Himalayan regions - Kaleem Mehmood; Shoaib Ahmad Anees; Sultan Muhammad; Gadah Albasher; Fahad Shahzad; Khadim Hussain; Qijing Liu; Rashid Ayub; Waseem Razzaq Khan (Stochastic Environmental Research and Risk Assessment, 2025)

PSA level 1 analysis by considering redundancy and diversity of emergency diesel generators for APR-1400 - Muhammad Zubair; Ronak Shahin Radkiany; Mahra Mohammad Aljaradi; Shamma Abdulla Alblooshi; Horeya Sultan Alhammadi; Yumna Akram (Annals of Nuclear Energy, 2025)

RETRACTED ARTICLE: Bond graph analysis of a three-link physiological motor control system: integrating simulation and muscle behavior - Armeen Saeed; Nadia Sultan; Najam-ul-Islam Muhammad; A. M. Mughal (Biological Cybernetics, 2025)

A comprehensive review on the bioactivity and pharmacological attributes of Withania somnifera - Muhammad Usman Khalid; Muhammad Tauseef Sultan; Iqra Baig; Asad Abbas; Ahmad Mujtaba Noman; Abdellah Zinedine; Elena Bartkiene; João Miguel Rocha (Natural Product Research, 2025)

Ostrich oil evaluation; Parallel to food and pharmaceutical industries requirements: A review - Shehnshah Zafar; Adnan Amjad; Muhammad Tauseef Sultan; Muhammad Mueed Tanveer Malik (Food and Humanity, 2025)

Asymmetric structure fabric-based energy manager for simultaneous power and steam generation - Zhenzhen Guo; Jiameng Zhang; Jichao Wang; Muneerah Alomar; Muhammad Sultan Irshad; Jinlong Wu; Chaoran Shi; Iftikhar Ahmed; Van-Duong Dao; Ruiqing Shi; Xiaochao Fan; Xianbao Wang (Desalination, 2025)

Predictive modeling of fractional plankton-assisted cholera propagation dynamics using Bayesian regularized deep cascaded exogenous neural networks - Adil Sultan; Muhammad Junaid Ali Asif Raja; Chuan-Yu Chang; Chi-Min Shu; Adiqa Kausar Kiani; Muhammad Asif Zahoor Raja (Process Safety and Environmental Protection, 2025)

Superhydrophilic wettability porous materials from construction tooil/water separation applications - Muhammad Naseem; Mansoor Sultan; Mazhar ul Islam; Abdul Kareem; Nisar Ali; Ibrahim Khan; Shakeel Ahmad; Farooq nawaz; Adnan Khan; Farman Ali; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; et al. (Fuel, 2025)

Structural and functional characterization of pyrabactin resistance 1-like (PYL) proteins and molecular docking analysis provides insight into stress tolerance in Sorghum bicolor - Muhammad Mudasir; Mirza Muhammad Ahad Baig; Yaqoob Sultan; Abdulsmad Baig (Genetic Resources and Crop Evolution, 2025)

Quest for environmental management and sustainability: Evaluating the drivers of territorial and consumption-based carbon emissions in G-20 economies - Muhammad Adnan Bashir; Li Qing; Shahid Manzoor; Shahzad Khan Durrani; Lin Jingting; Nasir Sultan (Journal of Environmental Management, 2025)

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

Enhancing Wheat Yield and Zinc Biofortification through Synergistic Action of Potent Zinc-Solubilizing Bacteria and Zinc Sulfate in Calcareous Soil - Murad Ali; Iftikhar Ahmed; Munir Hussain Zia; Saira Abbas; Tariq Sultan; Muhammad Sharif (Agricultural Research, 2025)

Corrigendum to “Uniformly dispersed flowery EuZrSe3 derived from the europium-based metal–organic framework for energy storage devices” [Fuel 336 (2023) 127066] - Abdul Ghafoor Abid; Soumaya Gouadria; Sumaira Manzoor; Khadijah Mohammed Saleh Katubi; Karam Jabbour; Muhammad Abdullah; Mehar Un Nisa; Salma Aman; Mohammed Sultan Al-Buriahi; Muhammad Naeem Ashiq (Fuel, 2025)

Intelligent predictive networks for nonlinear oxygen-phytoplankton-zooplankton coupled marine ecosystems under environmental and climatic disruptions - Adil Sultan; Muhammad Junaid Ali Asif Raja; Chuan-Yu Chang; Chi-Min Shu; Muhammad Shoaib; Adiqa Kausar Kiani; Muhammad Asif Zahoor Raja (Process Safety and Environmental Protection, 2025)

Residual effects of biochar and nano-modified biochar on growth and physiology under saline environment in two different genotype of Oryza sativa L. - Haider Sultan; Hafiz Muhammad Mazhar Abbas; Mohammad Faizan; Abolghassem Emamverdian; Asad Shah; Saraj Bahadur; Yusheng Li; Mohammad Nauman Khan; Lixiao Nie (Journal of Environmental Management, 2025)

Jellyfish–mimetic solar evaporator with polyelectrolyte skeleton for sustainable desalination under higher salinity - Shan Zhai; Fang Yu; Naila Arshad; Suji Huang; Junyang Tao; Changwen Li; Liangyou Lin; Jingwen Qian; Muhammad Sultan Irshad; Xianbao Wang (Desalination, 2025)

Microbial-inoculated biochar for remediation of salt and heavy metal contaminated soils - Hafiz Muhammad Mazhar Abbas; Ummah Rais; Muhammad Mohsin Altaf; Fahd Rasul; Asad Shah; Ashar Tahir; Muhammad Nafees-Ur-Rehman; Muhammad Shaukat; Haider Sultan; Ruilong Zou; Mohammad Nauman Khan; Lixiao Nie (Science of The Total Environment, 2024)

An assessment of the autotrophic/heterotrophic synergism in microalgae under mixotrophic mode and its contribution in high-rate phosphate recovery from wastewater - Rabail Zulekha; Muhammad Mubashar; Muhammad Muzamil Sultan; Zimin Wang; Jing Li; Xuezhi Zhang (Bioresource Technology, 2024)

Improving Irrigation Performance of Raised Bed Furrow Using WinSRFR Model - Muhammad Ayub Shah; Muhammad Waseem; Mudassar Iqbal; Ghulam Nabi; Muhammad Atiq Ur Rehman Tariq; Abu Bakar Arshed; Umar Sultan; Muhammad Laraib; Khawar Abbas (Water Conservation Science and Engineering, 2024)
Agricultural productivity is intricately tied to efficient water management strategies, with raised bed furrow systems being a prevalent method for irrigation. However, the optimization of these systems remains a critical area of exploration. The border irrigation method is commonly employed in developing countries for irrigation and leads to significant water loss, reduced irrigation efficiency, and increased irrigation durations. In contrast, raised bed furrow irrigation represents an improved surface irrigation technique that optimizes water usage in irrigated systems. This study seeks to assess the irrigation performance of raised bed furrows, encompassing deep percolation loss, distribution uniformity, adequacy, and application efficiency. The evaluation will be conducted for both existing conditions and an optimized scenario achieved through the application of the WinSRFR model. Field data facilitated the numerical simulation and the model was calibrated to reflect the existing irrigation system dynamics accurately. The performance of the model was assessed by utilizing the statistical indicator of root mean square error (RMSE) and revealed good agreement between advance and recession time. Results revealed that existing raised bed furrow irrigation exhibited up to 40% deep percolation loss, 80% distribution uniformity, and 60% application efficiency. Increasing furrow length had adverse effects; decreased application efficiency and distribution uniformity; and increased deep percolation losses. In contrast, reducing the furrow length and cutoff time by up to 33% and 40%, respectively, and increasing the width and inflow rate by up to 55% and 100%, respectively, enhanced the application efficiency and distribution uniformity, and minimized deep percolation loss. Overall, improved raised bed furrow irrigation provides a more efficient option and is encouraged to adopt for irrigation.

Spatial patterned solar evaporator for effective thermal management in enhanced solar-driven evaporation, and wastewater remediation - Naila Arshad; Muhammad Sohail Asghar; Muhammad Sultan Irshad; Najah Alwadie; Jinhua Li; M.A.K Yousaf Shah; Zhengbiao Ouyang; Hao Wang; Ho Xuan Nang; Van-Duong Dao; Xianbao Wang (Chemical Engineering Journal, 2024)

Impact of Drought Duration and Severity on Drought Recovery Period for Different Land Cover Types in Balochistan, Pakistan - Hayat Ullah Khan; Muhammad Waseem; Mudassar Iqbal; Faraz Ul Haq; Abu Bakar Arshed; Muhammad Laraib; Umar Sultan (Journal of the Indian Society of Remote Sensing, 2024)

Towards safer mining environments: an in-depth review of predictive models for accidents - Kausar Sultan Shah; Hafeez Ur Rehman; Niaz Muhammad Shahani; Barkat Ullah; Naeem Abbas; Muhammad Junaid; Mohd Hazizan bin Mohd Hashim (Arabian Journal of Geosciences, 2024)

Tailorable MBene aerogel with the lowest evaporation enthalpy for solar seawater desalination and wastewater purification - Junyang Tao; Naila Arshad; Muhammad Sultan Irshad; Muneerah Alomar; Fengshuai Zhu; Suji Huang; Shan Zhai; Van-Duong Dao; Xianbao Wang (Chemical Engineering Journal, 2024)

Temporal stress perturbations generated by the Kahramanmaraş Mw 7.8 & 7.5 2023 seismic doublet in Türkiye - Mohammad Tahir; Bilal Saif; Seema Tahir; Mahmood Sultan; Talat Iqbal; Muhammad Ali Shah (Acta Geophysica, 2024)

A novel solution for the in-situ Microcystis aeruginosa capture and flotation removal using fly ash derived buoyant cenospheres - Zimin Wang; Shi Zhang; Shaozhe Cheng; Haiyang Zhang; Muhammad Muzamil Sultan; Jing Li; Xuezhi Zhang (Journal of Cleaner Production, 2024)

Comprehensive chemical profiling with UHPLC-MS, in-vitro, in-silico, and in-vivo antidiabetic potential of Typha domingensis Pers; A novel source of bioactive compounds - Rizwana Dilshad; Kashif-ur-Rehman Khan; Rihana Dilshad; Saeed Ahmad; Huma Rao; Umair Khurshid; Sultan Ahmad; Maqsood Ahmad; Hafiz Muhammad Usman Abid; Muhammad Kashif Zaman; Rabia Nisar; Saharish Khaliq; et al. (South African Journal of Botany, 2024)

Exploring the variability of root system architecture under drought stress in heat-tolerant spring-wheat lines - Asadullah; Shahmir Ali Kalhoro; Wajid Farhad; Azhar Iqbal; Sultan; Abdul Waheed; Muhammad Rashid; Syed Rehmat Ullah Shah (Plant and Soil, 2024)
Background and aims Global wheat production is under threat due to climate change, specifically heat and drought and their combination. This study aims to address the root trait responses of heat-tolerant wheat genotypes to drought. Methods The variability in root traits of CIMMYT wheat lines, which were previously developed for heat stress tolerance (HTWL), was evaluated alongside 10 Pakistani-approved varieties under three cultivation conditions and soil moisture levels. Results Our findings revealed that the plasticity of the wheat root system is highly pronounced, with rhizosphere conditions exerting a more substantial influence (5–49%) than the genotypic response (1–14%). Furthermore, in the hydroponic and pot system, we noted higher maximum-root length (1.5–1.8 fold) and root-to-shoot ratio (3.4–10.6 fold) as compared to field condition, while the root biomass was substantially higher in the field trial (3-57 fold). Nonetheless, persistent drought conditions exerted contrasting impact with reduction in most of the traits except specific root length and harvest index which were increased under drought. Conclusions The variation in root traits against drought indicates the potential for the development of improved genotypes that can withstand multiple stresses. Furthermore, it is crucial to consider rhizosphere conditions when selecting genotypes, as the plasticity of wheat roots may lead to misinterpretations if rhizosphere conditions are disregarded. Root dry weight and root-to-shoot ratio are more stable traits as compared to maximum root length and specific root length. It is recommended to evaluate a broader range of rhizosphere conditions to select tolerant genotypes.

An innovative perovskite oxide enabling improved efficiency for low-temperature ceramic electrochemical cells - Yuzheng Lu; M. A. K. Yousaf Shah; Naveed Mushtaq; Muhammad Yousaf; Nabeela Akbar; Naila Arshad; Sultan Irshad (Fuel, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Recent synthetic approaches towards thienothiophenes: a potential template for biologically active compounds - Ayesha Rafiq; Sana Aslam; Matloob Ahmad; Muhammad Shahid Nazir; Ambar Farooq; Sadia Sultan (Molecular Diversity, 2024)

Structural and thermal investigation of lignocellulosic biomass conversion for enhancing sustainable imperative in progressive organic refinery paradigm for waste-to-energy applications - Tayyab Qureshi; Muhammad Farooq; Shahid Imran; Muhammad Adeel Munir; Muhammad Asad Javed; Ihsanullah Sohoo; Muhammad Sultan; Ateekh Ur Rehman; Muhammad Farhan; Muhammad Asim; John M. Andresen (Environmental Research, 2024)

A meta-analysis highlighting the increasing relevance of the hair matrix in exposure assessment to organic pollutants - Muhammad Junaid; Marriya Sultan; Shulin Liu; Naima Hamid; Qiang Yue; De-Sheng Pei; Jun Wang; Brice M.R. Appenzeller (Science of The Total Environment, 2024)

Biochar and nano biochar: Enhancing salt resilience in plants and soil while mitigating greenhouse gas emissions: A comprehensive review - Haider Sultan; Yusheng Li; Waqas Ahmed; Mu yixue; Asad Shah; Mohammad Faizan; Aqeel Ahmad; Hafiz Muhammad Mazhar Abbas; Lixiao Nie; Mohammad Nauman Khan (Journal of Environmental Management, 2024)

Empirical analysis of cost-effective and equitable solid waste management systems: Environmental and economic perspectives - Asif Iqbal; Abdullah Yasar; Abdul-Sattar Nizami; Rafia Haider; Imran Ali Sultan; Aman Anwer Kedwaii; Muhammad Murtaza Chaudhary; Muhammad Hassan Javed; Anees Ahmad; Khadija Sajid; Muhammad Naqvi; Muhammad Usman Ghori (Environmental Research, 2024)

Genome-wide screening and evolutionary analysis of ZIP (ZRT–IRT like proteins) family in cowpea (Vigna unguiculata L.) - Arif Ullah; Zamarud Shah; Iqbal Munir; Hamza Iqbal; Muhammad Zulfiqar Ahmad; Warda Sultan; Afrasyab Khan (Genetic Resources and Crop Evolution, 2024)

Characteristics of IDL and Es layers and the impact of increasing solar activity on their descent at the Arabian Peninsula - Muhammad Mubasshir Shaikh; Manar Anwer Khaleel Abusirdaneh; Sultan Suhail Halawa; Ilias Fernini (Advances in Space Research, 2024)

The untold story of PFAS alternatives: Insights into the occurrence, ecotoxicological impacts, and removal strategies in the aquatic environment - Naima Hamid; Muhammad Junaid; Marriya Sultan; Suman Thodhal Yoganandham; Ong Meng Chuan (Water Research, 2024)

Nickel uptake in leafy greens from contaminated soil: an investigation into phytoavailability and health risk assessment using in vitro digestion model - Sumbal Ammara; Muhammad Tariq Rafiq; Rukhsanda Aziz; Ying Feng; Sultan Mehmood; Mehwish Taneez; Muhammad Suhaib; Fatima Asif (Environmental Monitoring and Assessment, 2024)

Contribution to the pollen morphology of Astragalus L. section Aegacantha Bunge (Galegeae-Fabaceae) and its systematic significance - Amjad Khan; Mushtaq Ahmad; Amir Sultan; Zakir Ullah; Khawar Majeed; Tariq Ullah; Muhammad Zafar (Palynology, 2024)

Thermal performance of a solar heat collection and storage wall with night insulation in winter: A numerical study - Yafen Sun; Nan Zhang; Zhaoli Zhang; Muhammad Sultan; Yanping Yuan (Energy and Buildings, 2024)

Zinc Oxide Nanoparticles Significant Role in Poultry and Novel Toxicological Mechanisms - Arjmand Fatima; Tean Zaheer; Kaushik Pal; Rao Zahid Abbas; Tayyaba Akhtar; Sultan Ali; Muhammad Shahid Mahmood (Biological Trace Element Research, 2024)

Pathological effects of feeding aflatoxin-contaminated feed on immune status and reproductive performance of juvenile white leghorn males and its mitigation with ∝-tocopherol and Moringa oleifera - Muhammad Kashif Saleemi; Ahmad Raza; Aisha Khatoon; Muhammad Zubair; Shafia Tehseen Gul; Xu Yongping; Bilal Murtaza; Faqir Muhammad; Bushra Akhtar; Farhat Jubeen; Farzana Rizvi; Khawar Zubair; et al. (Environmental Science and Pollution Research, 2023)

An integrated assessment of ecological and human health risks of per- and polyfluoroalkyl substances through toxicity prediction approaches - Naima Hamid; Muhammad Junaid; Rakia Manzoor; Marriya Sultan; Ong Meng Chuan; Jun Wang (Science of The Total Environment, 2023)

Underground geological sequestration of carbon dioxide (CO2) and its effect on possible enhanced gas and oil recovery in a fractured reservoir of Eastern Potwar Basin, Pakistan - Anaiz Gul Fareed; Asif Hussain Khoja; Fabio De Felice; Antonella Petrillo; Muhammad Arsalan Sultan; Zafar Khan Jalalzai; Syed Sheraz Daood (Science of The Total Environment, 2023)

Synthesis of N-doped TiO2 nanoparticles with enhanced photocatalytic activity for 2,4-dichlorophenol degradation and H2 production - Javed Ali Khan; Murtaza Sayed; Noor S. Shah; Sanaullah Khan; Ashfaq Ahmad Khan; Muhammad Sultan; Ammar M. Tighezza; Jibran Iqbal; Grzegorz Boczkaj (Journal of Environmental Chemical Engineering, 2023)

ZnO nanoparticles mediated by Azadirachta indica as nano fertilizer: Improvement in physiological and biochemical indices of Zea mays grown in Cr-contaminated soil - Sajid Mehmood; Wenjie Ou; Waqas Ahmed; Jochen Bundschuh; Muhammad Rizwan; Mohsin Mahmood; Haider Sultan; Juha M. Alatalo; Ahmed S.M. Elnahal; Wenjie Liu; Weidong Li (Environmental Pollution, 2023)

Enhancing solar steam generation in hydrogel evaporator by bio-based microfluidic component - Changyuan Song; Muhammad Sultan Irshad; Zhengtong Li; Junhua Hu; Guosheng Shao; Wentao Liu; Xingtao Xu (Chemical Engineering Journal, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

National strategy for climate change adaptability: a case study of extreme climate-vulnerable countries - Noman Arshed; Muhammad Ibrahim Saeed; Sultan Salem; Uzma Hanif; Manzir Abbas (Environment, Development and Sustainability, 2023)

A critical review on efficient thermal environment controls in indoor vertical farming - Md Shamim Ahamed; Muhammad Sultan; Danielle Monfet; Md Sazan Rahman; Ying Zhang; Azlan Zahid; Muhammad Bilal; T.M. Abir Ahsan; Yasmine Achour (Journal of Cleaner Production, 2023)

Exploring perovskite oxide for advancing salt-resistant photothermal membranes and reliable thermoelectric generators - Naila Arshad; Muhammad Sultan Irshad; Muneerah Alomar; Jinming Guo; M. Sohail Asghar; Naveed Mushtaq; M.A.K. Yousaf; Uzma Ghazanfar; Matiullah Shah; Xianbao Wang; Yabin Hao; Lien Thi Do; et al. (Chemical Engineering Journal, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Application of teleseismic receiver functions and gravity for Moho depth mapping: a case study of the Western Himalayas - Mohammad Salam; Jamil Ahmad; Waqar Ali Zafar; Muhammad Tahir Iqbal; Imran Khan; Amir Sultan; Talat Iqbal (Arabian Journal of Geosciences, 2023)

A Comparative Study of the Influence of Volumetric Joint Counts (Jv) and Resistivity on Rock Quality Designation (RQD) Using Multiple Linear Regression - Muhammad Junaid; Rini Asnida Abdullah; Radzuan Sa’ari; Kausar Sultan Shah; Rafi Ullah (Pure and Applied Geophysics, 2023)

Composted Melia azedarach L. (Chinaberry tree) Sawdust Mixtures Regulate the Sprouting and Growth of Single Bud Node Seedlings of Sugarcane - Mehwish Sultan Ahmed; Muhammad Yasin; Muhammad Usman Zia; Muhammad Ather Nadeem; Sher Muhammad; Athar Mahmood (Journal of Soil Science and Plant Nutrition, 2023)

The changing landscape of agriculture: role of precision breeding in developing smart crops - Amna Chaudhry; Ahtsham Ul Hassan; Sultan Habibullah Khan; Asim Abbasi; Aiman Hina; Muhammad Tajammal Khan; Nader R. Abdelsalam (Functional & Integrative Genomics, 2023)

High internal phase-phase change composites for customized thermal management and anti-counterfeiting - Zhuoya Jia; Chao Chen; Youshuang Zhou; Muhammad Sultan Irshad; Qunchao Zhang; Tao Jiang; Dean Shi; Jun You (Chemical Engineering Journal, 2023)

Uniformly dispersed flowery EuZrSe3 derived from the europium-based metal–organic framework for energy storage devices - Abdul Ghafoor Abid; Soumaya Gouadria; Sumaira Manzoor; Khadijah Mohammed Saleh Katubi; Karam Jabbour; Muhammad Abdullah; Mehar Un Nisa; Salma Aman; Mohammed Sultan Al-Buriahi; Muhammad Naeem Ashiq (Fuel, 2023)

A vortex-induced vibration-based self-tunable airfoil-shaped piezoelectric energy harvester for remote sensing applications in water - Muhammad Hafizh; Asan G.A. Muthalif; Jamil Renno; M.R. Paurobally; Mohamed Sultan Mohamed Ali (Ocean Engineering, 2023)

Highly charged solar evaporator toward sustainable energy transition for in-situ freshwater & power generation - Muhammad Sultan Irshad; Yabin Hao; Naila Arshad; Muneerah Alomar; Liangyou Lin; Xiuqiang Li; Swelm. Wageh; Omar A. Al-Hartomy; Abdullah G. Al-Sehemi; Van-Duong Dao; Hao Wang; Xianbao Wang; et al. (Chemical Engineering Journal, 2023)

Clinical pharmacokinetics of terbutaline in humans: a systematic review - Khadeeja Sultan; Ammara Zamir; Waseem Ashraf; Imran Imran; Hamid Saeed; Anees ur Rehman; Abdul Majeed; Muhammad Fawad Rasool (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Factorial analysis for the impact on filtration properties of water-based drilling fluid after the addition of graphene oxide, pure-bore, and sodium alginate - Shaine Mohammadali Lalji; Syed Imran Ali; Muhammad Mohsin Yousufi; Muhammad Arsalan Sultan; Khizra Fatima; Abdur Rahman Misbah (Arabian Journal of Geosciences, 2023)

Profiling of phthalates, brominated, and organophosphate flame retardants in COVID-19 lockdown house dust; implication on the human health - Nadeem Ali; Muhammad Imtiaz Rashid; Nabil A. Alhakamy; Sultan Hassan Alamri; Syed Ali Musstjab Akber Shah Eqani (Science of The Total Environment, 2023)

Recent Advances and Treatment of Emerging Contaminants Through the Bio-assisted Method: A Comprehensive Review - Abdul Sattar Jatoi; Jawad Ahmed; Faheem Akhter; Syed Haseeb Sultan; Ghulam Sever Chandio; Shoaib Ahmed; Zubair Hashmi; Muhammad Azam Usto; Muhammad Shuaib Shaikh; Muhammad Siddique; Ghulamullah Maitlo (Water, Air, & Soil Pollution, 2023)

Biochemical Characterization and Potential of Bacillus safensis Strain SCAL1 to Mitigate Heat Stress in Solanum lycopersicum L. - Tehmeena Mukhtar; Fawad Ali; Mazhar Rafique; Javed Ali; Muhammad Siddique Afridi; Donald Smith; Shehzad Mehmood; Amna; Alfred Souleimanov; Ghulam Jellani; Tariq Sultan; Farooq Hussain Munis; et al. (Journal of Plant Growth Regulation, 2023)

Genetic diversity and population structure assessed through simple sequence repeat markers in Saccharum spp. hybrids from Pakistan and Sri Lanka - Sundas Shahzad; Muhammad Saeed; Shagufta Perveen; Muhammad Azeem; Iqra Sajjad; Shazia Saeed; Muhammad Naeem; Alia Javed; Iqra Sultan; Ukasha Faria; Sana Maryam; Muhammad Zaid Yousaf (Genetic Resources and Crop Evolution, 2022)

Evaluating the thermal-cooling induced effects on the Ambela granite properties (from Pakistan) using experimental and image processing techniques - Naseer Muhammad Khan; Liqiang Ma; Kewang Cao; Sajjad Hussain; Asghar Ali; Wei Liu; Saad S. Alarifi; Kausar Sultan shah; Sajid Khan; Yang Xiaoxu; Yujun Xu (Bulletin of Engineering Geology and the Environment, 2022)

Quantification of Rock Mass Condition Based on Fracture Frequency Using Unmanned Aerial Vehicle Survey for Slope Stability Assessment - Muhammad Junaid; Rini Asnida Abdullah; Radzuan Sa’ari; Hafeezur Rehman; Kausar Sultan Shah; Rafi Ullah; Mohd Nur Asmawisham Alel; Ir. Zuraini Zainal; Nurul Eilmy Zainuddin (Journal of the Indian Society of Remote Sensing, 2022)

Quantitative estimation of essential/toxic elemental levels in the serum of esophagus cancer patients in relation to controls - Muhammad Abdul Qayyum; Muhammad Habib Sultan; Zahid Farooq; Khawaja Muddassir; Tahir Farooq; Ahmad Irfan (Environmental Science and Pollution Research, 2022)

A comparative analysis of renewable and non-renewable energy generation to relegate CO2 emissions and general costs in household systems - Mudassar Hussain; Manzoor Sultan; Faiza Uzma; Cheng Longsheng; Muhammad Yousaf Malik; Abdul Rahman Butt; Aqsa Sajjad; Ijaz Younis; Muhammad Imran (Environmental Science and Pollution Research, 2022)

Green growth and environmental quality in top polluted economies: the evolving role of financial institutions and markets - Xiaomeng Deng; Juan Yang; Zahoor Ahmed; Muhammad Hafeez; Sultan Salem (Environmental Science and Pollution Research, 2022)

Robust segmentation of underwater fish based on multi-level feature accumulation - Adnan Haider; Muhammad Arsalan; Jiho Choi; Haseeb Sultan; Kang Ryoung Park (Frontiers in Marine Science, 2022)
Because fish are vital to marine ecosystems, monitoring and accurate detection are crucial for assessing the potential for fisheries in these environments. Conventionally, fish-related assessment is conducted manually, which makes it labor-intensive and time-consuming. In addition, the assessments are challenging owing to underwater visibility limitations, which leads to poor detection accuracy. To overcome these problems, we propose two novel architectures for the automatic and high-performance segmentation of fish populations. In this study, the efficient fish segmentation network (EFS-Net) and multi-level feature accumulation-based segmentation network (MFAS-Net) are the base and final networks, respectively. In deep convolutional neural networks, the initial layers usually contain potential spatial information. Therefore, the EFS-Net employs a series of convolution layers in the early stage of the network for optimal feature extraction. To boost segmentation accuracy, the MFAS-Net uses an initial feature refinement and transfer block to refine potential low-level information and subsequently transfers it to the deep stages of the network. Moreover, the MFAS-Net employs multi-level feature accumulation that improves pixel-wise prediction for fish that are indistinct. The proposed networks are evaluated using two publicly available datasets, namely DeepFish and semantic segmentation of underwater imagery (SUIM), both of which contain challenging underwater fish segmentation images. The experimental results reveal that mean intersection-over-unions of 76.42% and 92.0% are attained by the proposed method for the DeepFish and SUIM datasets, respectively; these values are higher than those by the state-of-the-art methods such as A-LCFCN+PM and DPANet. In addition, high segmentation performance is achieved without compromising the computational efficiency of the networks. The MFAS-Net requires only 3.57 million trainable parameters to be fully trained. The proposed model and the complete code will be made available 1 .

Triggering mechanisms of Gayari avalanche, Pakistan - Bilal Saif; Mohammad Tahir; Amir Sultan; Muhammad Tahir Iqbal; Talat Iqbal; Muhammad Ali Shah; Samia Gurmani (Natural Hazards, 2022)

Combined efficacy of Cinnamomum zeylanicum and doxorubicin against leukemia through regulation of TRAIL and NF-kappa B pathways in rat model - Sidra Bukhari; Muhammad Hamid Siddique; Anum Naeem; InamUllah Khan; Zain Ali; Asiya Essa; Falak Fazal; Riffat Aysha Anis; Lukas Moran; Aneesa Sultan; Iram Murtaza; Petr Vanhara; et al. (Molecular Biology Reports, 2022)

Prediction of Type 2 Diabetes at Pre-diabetes Stage by Mass Spectrometry: A Preliminary Study - Saria Tariq; Munazza Raza Mirza; Muhammad Iqbal Choudhary; Rabia Sultan; Muneeza Zafar (International Journal of Peptide Research and Therapeutics, 2022)

Water-saturated zone recognition using integrated 2D electrical resistivity tomography, borehole, and aerial photogrammetry in granite deposit, Malaysia - Muhammad Junaid; Rini Asnida Abdullah; Radzuan Sa’ari; Wahid Ali; Hafeezur Rehman; kausar Sultan Shah; Mahmut Sari (Arabian Journal of Geosciences, 2022)

Heavy metal remediation and resistance mechanism of Aeromonas , Bacillus , and Pseudomonas : A review - Ali Fakhar; Bushra Gul; Ali Raza Gurmani; Shah Masaud Khan; Shafaqat Ali; Tariq Sultan; Hassan Javed Chaudhary; Mazhar Rafique; Muhammad Rizwan (Critical Reviews in Environmental Science and Technology, 2022)

Characterization of functional genes GS3 and GW2 and their effect on the grain size of various landraces of rice (Oryza sativa) - Haroon Rasheed; Sajid Fiaz; Muhammad Abid Khan; Sultan Mehmood; Faizan Ullah; Sumbul Saeed; Shahid Ullah Khan; Tabassam Yaseen; Reem M. Hussain; Abdul Qayyum (Molecular Biology Reports, 2022)

Collaborative-trust approach toward malicious node detection in vehicular ad hoc networks - Shahid Sultan; Qaisar Javaid; Arif Jamal Malik; Fadi Al-Turjman; Muhammad Attique (Environment, Development and Sustainability, 2022)

Imaging of rupture process of 2005 Mw 7.6 Kashmir earthquake using back projection techniques - Mahmood Sultan; Farhan Javed; Muhammad Fahad Mahmood; Muhammad Ali Shah; Khawar Ashfaq Ahmed; Talat Iqbal (Arabian Journal of Geosciences, 2022)

3-Dimensional membrane capsules: Synthesis modulations for the remediation of environmental pollutants – A critical review - Imran Ali; Juying Li; Changsheng Peng; Muhammad Qasim; Zahid M. Khan; Iffat Naz; Muhammad Sultan; Muhammad Rauf; Waheed Iqbal; Hafiz Muhammad Adeel Sharif (Critical Reviews in Environmental Science and Technology, 2022)

Nanocrystals: Characterization Overview, Applications in Drug Delivery, and Their Toxicity Concerns - Mohammed Asadullah Jahangir; Syed Sarim Imam; Abdul Muheem; Ananda Chettupalli; Fahad A. Al-Abbasi; Muhammad Shahid Nadeem; Imran Kazmi; Muhammad Afzal; Sultan Alshehri (Journal of Pharmaceutical Innovation, 2022)

Genetic dissection of grain yield traits in a large collection of spring wheat (Triticum aestivum L.) germplasm - Sultan Habibullah Khan; Muhammad Sajjad; Saima Gulnaz; Sundas Waqar; Munawar Shahzad; Saima Mir Arain (Journal of Crop Science and Biotechnology, 2022)

Mapping sequences and mineral deposits in poorly exposed lithologies of inaccessible regions in Azad Jammu and Kashmir using SVM with ASTER satellite data - Muhammad Imran; Sultan Ahmad; Amir Sattar; Aqil Tariq (Arabian Journal of Geosciences, 2022)

Anti-Huntington’s Effect of Butin in 3-Nitropropionic Acid-Treated Rats: Possible Mechanism of Action - Sultan Alshehri; Fahad A. Al-Abbasi; Mohammed M. Ghoneim; Syed Sarim Imam; Muhammad Afzal; Khalid Saad Alharbi; Muhammad Shahid Nadeem; Nadeem Sayyed; Imran Kazmi (Neurotoxicity Research, 2022)

Characterization of new COBRA like (COBL) genes in wheat (Triticum aestivum) and their expression analysis under drought stress - Muhammad Zaheer; Shoaib Ur Rehman; Sultan Habibullah Khan; Shahmeer Shahid; Awais Rasheed; Rabia Naz; Muhammad Sajjad (Molecular Biology Reports, 2022)

Metadherin (MTDH) overexpression significantly correlates with advanced tumor grade and stages among colorectal cancer patients - Aimen Sultan; Namood-E Sahar; Syeda Kiran Riaz; Javeria Qadir; Shahzad Hussain Waqar; Farhan Haq; Tanwir Khaliq; Muhammad Faraz Arshad Malik (Molecular Biology Reports, 2021)

Does digitalization matter in green preferences in nexus of output volatility and environmental quality? - Carlos Samuel Ramos-Meza; Rinat Zhanbayev; Hazrat Bilal; Mubbashra Sultan; Zehra Betül Pekergin; Hafiz Muhammad Arslan (Environmental Science and Pollution Research, 2021)

Implication of Remote Sensing Data under GIS Environment for Appraisal of Irrigation System Performance - Sultan Ahmad Rizvi; Afeef Ahmad; Muhammad Latif; Abdul Sattar Shakir; Aftab Ahmad Khan; Waqas Naseem; Muhammad Riaz Gondal (Water Resources Management, 2021)

Experimental and comparative study of Chinese commercial improved coal-fired cooking and space-heating stoves - Riaz Ahmad; Adnan Abbas; Wang Jufei; Li Hua; Muhammad Sultan; Bohong Li; Samuel M Nyambura; Pan Xingjia (Environmental Science and Pollution Research, 2021)

Phytochemical and spectral analysis of the methanolic extracts of leaves of Murraya koenigii of Jazan, Saudi Arabia - Sivakumar Sivagurunthan Moni; Muhammad Hadi Sultan; Hafiz A. Makeen; Aamena Jabeen; Syeda Sanobar; Rahimullah Siddiqui; Zia ur Rehman; Md Shamsher Alam; Sarfaraz Ahmad; Mohamed Eltaib Elmobark; Remesh Moochikkal (Natural Product Research, 2021)

Nonlinear postural control paradigm for larger perturbations in the presence of neural delays - Nadia Sultan; Muhammad Najam ul Islam; Asif Mahmood Mughal (Biological Cybernetics, 2021)

Comparative toxicity of transgenic cotton CEM-33, Bt-906 varieties, and Annona squamosa L., seed extract against biotic potential of Spodoptera litura (Fab.) - Qurban Ali Arain; Muhammad Farhanullah Khan; Habibullah Rana; Amjad Sultan; Zubair Ahmed; Hakim Ali Sahito; Muhammad Asif Farooq; Muhammad Faheem Akbar; Tasneem Kousar (International Journal of Tropical Insect Science, 2021)

Enhancing socioeconomic resilience and climate adaptation through value chain development of mountain products in Hindu Kush Himalayas - Saranjam M. Baig; Aftab A. Khan; Amjad Ali; Muhammad Zafar Khan; Sultan Ahmed; Ghulam M. Shah; Ghulam Ali (Environment, Development and Sustainability, 2021)

Micro-morphological response of some native dicotyledonous species to particulate pollutants emitted from stone crushing activities - Iftikhar Ahmad; Lubaba Shamsi; Mansoor Hameed; Sana Fatima; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Anum Javaid; Muhammad Asim Sultan (Environmental Science and Pollution Research, 2021)

Solvent extraction, spectral analysis and antibacterial activity of the bioactive crystals of Sargassum aquifolium (Turner) C.Agardh from Red Sea - Sivakumar Sivagurunathan Moni; Mohammad Firoz Alam; Hafiz A. Makeen; Hassan A. Alhazmi; Muhammad Sultan; Rahimullah Siddiqui; Aamena Jabeen; Syeda Sanobar; Md Shamsher Alam; Zia Ur Rehman; Mohamed Eltyep Elmobark; Osama Madkhali; et al. (Natural Product Research, 2021)

Potential of Natural Bioactive Compounds in Management of Diabetes: Review of Preclinical and Clinical Evidence - Ameeduzzafar Zafar; Nabil K. Alruwaili; Dibya Sundar Panda; Syed Sarim Imam; Khalid Saad Alharbi; Muhammad Afzal; Khaled Shalaby; Imran Kazmi; Sultan Alshehri (Current Pharmacology Reports, 2021)

Landslides assessment using geophysical and passive radon exhalation detection techniques in Murree Hills, northern Pakistan: Implication for environmental hazard assessment - Khawar Ashfaq Ahmed; Sarfraz Khan; Mahmood Sultan; Umair Bin Nisar; Muhammad Rizwan Mughal; Shahid Nadeem Qureshi (Journal of Earth System Science, 2020)

Mechanistic Approaches of Internalization, Subcellular Trafficking, and Cytotoxicity of Nanoparticles for Targeting the Small Intestine - Asadullah Madni; Sadia Rehman; Humaira Sultan; Muhammad Muzamil Khan; Faiz Ahmad; M. Rafi Raza; Nadia Rai; Farzana Parveen (AAPS PharmSciTech, 2020)

Identification of Edible Fish Species of Pakistan Through DNA Barcoding - Muhammad Zubair Ghouri; Muhammad Ismail; Muhammad Asif Javed; Sultan Habibullah Khan; Nayla Munawar; Abdullah Bin Umar; Mehr-un-Nisa; Syed Ovais Aftab; Shazia Amin; Zulqurnain Khan; Aftab Ahmad (Frontiers in Marine Science, 2020)

The potential of Allium sativum and Cannabis sativa extracts for anti-tick activities against Rhipicephalus (Boophilus) microplus - Nasreen Nasreen; Sadaf Niaz; Adil Khan; Muhammad Arfan Zaman; Sultan Ayaz; Huma Naeem; Nasrullah Khan; Abdallah M. Elgorban (Experimental and Applied Acarology, 2020)

Analysis of coal-related energy consumption in Pakistan: an alternative energy resource to fuel economic development - Muhammad Yousaf Raza; Muhammad Tauqir Sultan Shah (Environment, Development and Sustainability, 2020)

Effect of particle morphology on mechanical behavior of rock mass - Kausar Sultan Shah; Mohd Hazizan bin Mohd Hashim; Muhammad Zaka Emad; Kamar Shah bin Ariffin; Muhammad Junaid; Naseer Muhammad Khan (Arabian Journal of Geosciences, 2020)

Formulation of Chitosan Polymeric Vesicles of Ciprofloxacin for Ocular Delivery: Box-Behnken Optimization, In Vitro Characterization, HET-CAM Irritation, and Antimicrobial Assessment - Ameeduzzafar; Nabil K Alruwaili; Syed Sarim Imam; Nasser Hadal Alotaibi; Nabil A. Alhakamy; Khalid Saad Alharbi; Sultan Alshehri; Muhammad Afzal; Sattam Khulaif Alenezi; Syed Nasir Abbas Bukhari (AAPS PharmSciTech, 2020)

Salivary Proteomic Analysis of Betel Nut (Areca catechu) Consumers by Mass Spectrometry Revealed Primary Indication of Oral Malignancies - Rabia Sultan; Munazza Raza Mirza; Muhammad Iqbal Choudhary; Mehtab Alam; Ikram-ul Haque (International Journal of Peptide Research and Therapeutics, 2020)

Testing the effect of different insecticides on Myzus persicae (Homoptera: Aphididae) in field mustard (Brassicae campestris L.) Czern for possible consideration in an IPM strategy - Muhammad Shahbaz Khan; Muhammad Faheem Akbar; Amjad Sultan; Muhammad Shoaib Saleem; Chand Gul (International Journal of Tropical Insect Science, 2020)

Migration and Household Adaptation in Climate-Sensitive Hotspots in South Asia - Amina Maharjan; Ricardo Safra de Campos; Chandni Singh; Shouvik Das; Arjun Srinivas; Mohammad Rashed Alam Bhuiyan; Sultan Ishaq; Muhammad Awais Umar; Tanzina Dilshad; Krity Shrestha; Suruchi Bhadwal; Tuhin Ghosh; et al. (Current Climate Change Reports, 2020)
Purpose of Review South Asia is highly vulnerable to the impacts of climate change, owing to the high dependency on climate-sensitive livelihoods and recurrent extreme events. Consequently, an increasing number of households are adopting labour migration as a livelihood strategy to diversify incomes, spread risks, and meet aspirations. Under the Collaborative Adaptation Research Initiative in Africa and Asia (CARIAA) initiative, four research consortia have investigated migration patterns and their inherent linkages to adaptation to climate change in climate hotspots. This article synthesizes key findings in regional context of South Asia. Recent Findings The synthesis suggests that in climate-sensitive hotspots, migration is an important livelihood diversification strategy and a response to various risks, including climate change. Typically, one or more household members, often young men, migrated internally or internationally to work in predominantly informal sectors. Remittances helped spatially diversify household income, spread risks, and insure against external stressors. The outcomes of migration are often influenced by who moves, where to, and what capacities they possess. Summary Migration was found to help improve household adaptive capacity, albeit in a limited capacity. Migration was mainly used as a response to risk and uncertainty, but with potential to have positive adaptation co-benefits.

Delineation of regional groundwater vulnerability using DRASTIC model for agricultural application in Pakistan - Aamir Shakoor; Zahid M. Khan; Hafiz U. Farid; Muhammad Sultan; Ijaz Ahmad; Naveed Ahmad; Muhammad H. Mahmood; Muhammad U. Ali (Arabian Journal of Geosciences, 2020)

A global prospective of environmental degradations: economy and finance - Muhammad Hafeez; Chunhui Yuan; Qiuyan Yuan; Zhang Zhuo; David Stromaier; Almalki Sultan Musaad O (Environmental Science and Pollution Research, 2019)

Acaricidal efficacy of Calotropis procera (Asclepiadaceae) and Taraxacum officinale (Asteraceae) against Rhipicephalus microplus from Mardan, Pakistan - Adil Khan; Nasreen Nasreen; Sadaf Niaz; Sultan Ayaz; Huma Naeem; Ijaz Muhammad; Fazal Said; Robert D. Mitchell; Adalberto A. Pérez de León; Snehil Gupta; Sachin Kumar (Experimental and Applied Acarology, 2019)

Carbon mineralization in subtropical dryland soil amended with different biochar sources - Sehar Sultan; Khalid Saifullah Khan; Muhammad Akmal; Zammurad Iqbal Ahmed; Qaiser Hussain; Shahab Ahmad Khosa (Arabian Journal of Geosciences, 2019)

Effects of Rhizophagus clarus and biochar on growth, photosynthesis, nutrients, and cadmium (Cd) concentration of maize (Zea mays) grown in Cd-spiked soil - Mazhar Rafique; Ibrahim Ortas; Muhammad Rizwan; Tariq Sultan; Hassan Javed Chaudhary; Mehmet Işik; Oğuzhan Aydin (Environmental Science and Pollution Research, 2019)

Input Selection of Wavelet-Coupled Neural Network Models for Rainfall-Runoff Modelling - Muhammad Shoaib; Asaad Y. Shamseldin; Sher Khan; Muhammad Sultan; Fiaz Ahmad; Tahir Sultan; Zakir Hussain Dahri; Irfan Ali (Water Resources Management, 2019)

Correction to: An efficient protocol for the synthesis of highly sensitive indole imines utilizing green chemistry: optimization of reaction conditions - Bushra Nisar; Syeda Laila Rubab; Abdul Rauf Raza; Sobia Tariq; Sana Jamshaid; Ayesha Sultan; Muhammad Nawaz Tahir (Molecular Diversity, 2019)

Occurrence of Aflatoxin M1 in raw and processed milk and assessment of daily intake in Lahore, Multan cities of Pakistan - Mateen Ahmad; Muhammad Awais; Shinawar Waseem Ali; Hafiz Azhar Ali Khan; Muhammad Riaz; Asif Sultan; Muhammad Shakeel Bashir; Adnan Ishtiaq Chaudhry (Food Additives & Contaminants Part B-Surveillance, 2019)

Moderating and mediating role of renewable energy consumption, FDI inflows, and economic growth on carbon dioxide emissions: evidence from robust least square estimator - Saiqa Naz; Rashida Sultan; Khalid Zaman; Abdullah Mohammed Aldakhil; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2019)

Earthworms as plug flow reactors: a first-order kinetic study on the gut of the vermicomposting earthworm Eudrilus eugeniae - Katheem Kiyasudeen; Mahamad Hakimi Ibrahim; Syahidah Akmal Muhammad; Sultan Ahmed Ismail; Fadzil Noor Gonawan; Mark Harris Zuknik (Environmental Science and Pollution Research, 2018)

An efficient protocol for the synthesis of highly sensitive indole imines utilizing green chemistry: optimization of reaction conditions - Bushra Nisar; Syeda Laila Rubab; Abdul Rauf Raza; Sobia Tariq; Ayesha Sultan; Muhammad Nawaz Tahir (Molecular Diversity, 2018)

A novel mutation in RDH5 gene causes retinitis pigmentosa in consanguineous Pakistani family - Neelam Sultan; Irfan Ali; Shazia Anwer Bukhari; Shahid Mahmood Baig; Muhammad Asif; Muhammad Qasim; Muhammad Imran Naseer; Mahmood Rasool (Genes & Genomics, 2018)

Therapeutic potential of dairy bioactive peptides: A contemporary perspective - Saira Sultan; Nuzhat Huma; Masood Sadiq Butt; Muhammad Aleem; Munawar Abbas (Critical Reviews in Food Science and Nutrition, 2018)

A Comparative Study of Various Hybrid Wavelet Feedforward Neural Network Models for Runoff Forecasting - Muhammad Shoaib; Asaad Y. Shamseldin; Sher Khan; Mudasser Muneer Khan; Zahid Mahmood Khan; Tahir Sultan; Bruce W. Melville (Water Resources Management, 2018)

Prevalence of antibodies to Neospora caninum in the serum of camels (Camelus dromedarius) from central Punjab, Pakistan - Muhammad Mudasser Nazir; Muhammad Oneeb; Muhammad Mazhar Ayaz; Fehmeeda Bibi; Atif Nisar Ahmad; Abdul Waheed; Muhammad Afzal Sajid; Muhammad Tauseef Sultan; Ghulam Yasin; David S. Lindsay (Tropical Animal Health and Production, 2017)

Use of TALEs and TALEN Technology for Genetic Improvement of Plants - Zulqurnain Khan; Sultan Habibullah Khan; Muhammad Salman Mubarik; Bushra Sadia; Aftab Ahmad (Plant Molecular Biology Reporter, 2017)

Prospective study of avian influenza H9 infection in commercial poultry farms of Punjab Province and Islamabad Capital Territory, Pakistan - Mamoona Chaudhry; Maqbool Ahmad; Hamad Bin Rashid; Bakhat Sultan; Haroon Rashid Chaudhry; Aayesha Riaz; Muhammad Shabir Shaheen (Tropical Animal Health and Production, 2017)

The role of new eudesmane-type sesquiterpenoid and known eudesmane derivatives from the red alga Laurencia obtusa as potential antifungal–antitumour agents - Walied M. Alarif; Khalid O. Al-Footy; Muhammad Sulaiman Zubair; Mohamed Halid PH; Mohamed A. Ghandourah; Salim A. Basaif; Sultan S. Al-Lihaibi; Seif-Eldin N. Ayyad; Farid A. Badria (Natural Product Research, 2016)

Biofunctional properties of Eruca sativa Miller (rocket salad) hydroalcoholic extract - Khushbakht Sultan; Muhammad Zakir; Haroon Khan; Abdur Rauf; Noor Ul Akber; Murad Ali Khan (Natural Product Research, 2016)

A review of steroids from Sarcophyton species - Muhammad Sulaiman Zubair; Khalid O. Al-Footy; Seif-Eldin N. Ayyad; Sultan S. Al-Lihaibi; Walied M. Alarif (Natural Product Research, 2016)

Wheat Allergy and Intolerence; Recent Updates and Perspectives - Imran Pasha; Farhan Saeed; Muhammad Tauseef Sultan; Rizwana Batool; Mahwash Aziz; Waqas Ahmed (Critical Reviews in Food Science and Nutrition, 2016)

Water quality and sediment assessment of Manchar Lake, Sindh, Pakistan: after effects of the super flood of 2010 - Taj Muhammad Jahangir; Muhammad Yar Khuhawar; Sultan Mahmood Leghari; Muhammad Tariq Mahar; Khalida Parveen Mahar (Arabian Journal of Geosciences, 2015)

Protein–Energy Malnutrition: A Risk Factor for Various Ailments - Rizwana Batool; Masood Sadiq Butt; Muhammad Tauseef Sultan; Farhan Saeed; Rabia Naz (Critical Reviews in Food Science and Nutrition, 2015)

Black Pepper and Health Claims: A Comprehensive Treatise - Masood Sadiq Butt; Imran Pasha; Muhammad Tauseef Sultan; Muhammad Atif Randhawa; Farhan Saeed; Waqas Ahmed (Critical Reviews in Food Science and Nutrition, 2013)

The low down on association mapping in hexaploid wheat (Triticum aestivum L.) - Muhammad Sajjad; Sultan Habibullah Khan; Abdul Mujeeb Kazi (Journal of Crop Science and Biotechnology, 2012)

Effect of Mineral Fortification on Plasma Biochemical Profile in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; Munammad Tauseef Sultan; Muhammad Riaz; Anwaar Ahmed (Biological Trace Element Research, 2011)

Arabinoxylans and Arabinogalactans: A Comprehensive Treatise - Farhan Saeed; Imran Pasha; Faqir Muhammad Anjum; Muhammad Tauseef Sultan (Critical Reviews in Food Science and Nutrition, 2011)

Nigella sativa : Reduces the Risk of Various Maladies - Masood Sadiq Butt; Muhammad Tauseef Sultan (Critical Reviews in Food Science and Nutrition, 2010)

Nutrient digestibility and feedlot performance of lambs fed diets varying protein and energy contents - Javed I. Sultan; Asif Javaid; Muhammad Aslam (Tropical Animal Health and Production, 2010)

Garlic: Nature's Protection Against Physiological Threats - Masood Sadiq Butt; Muhammad Tauseef Sultan; Mehmood S. Butt; Javaid Iqbal (Critical Reviews in Food Science and Nutrition, 2009)

Green Tea: Nature's Defense against Malignancies - Masood Sadiq Butt; Muhammad Tauseef Sultan (Critical Reviews in Food Science and Nutrition, 2009)

Heavy Metal Residues in the Milk of Cattle and Goats During Winter Season - Ijaz Javed; Ibadullah Jan; Faqir Muhammad; Zia-ur-Rahman; M. Zargham Khan; Bilal Aslam; Javed Iqbal Sultan (Bulletin of Environmental Contamination and Toxicology, 2009)